`\left(x-h\right)^{2}=4a\left(y-k\right)` left parenthesis, negative 2.3 6 , 4.4 3 , right parenthesis−2.36,4.43
Label:
5
Expression 6: left parenthesis, "x" minus "h" , right parenthesis squared equals negative 4 "a" left parenthesis, "y" minus "k" , right parenthesisx−h2=−4ay−k
6
`\left(x-h\right)^{2}=-4a\left(y-k\right)` left parenthesis, 1.9 6 , negative 4.2 , right parenthesis1.96,−4.2
Label:
7
8
powered by
powered by
left parenthesis, "x" minus "h" , right parenthesis squared equals 4 "a" left parenthesis, "y" minus "k" , right parenthesisx−h2=4ay−k
left parenthesis, "x" minus "h" , right parenthesis squared equals negative 4 "a" left parenthesis, "y" minus "k" , right parenthesisx−h2=−4ay−k